STRATEGI POLITIK EMMANUEL MACRON DALAM MEMENANGKAN SUARA MUSLIM DI PEMILU PRANCIS 2017 - Anggia, Priska; Fahmi, Ami Abdullah; Mulyana, Agus (Jazirah: Jurnal Peradaban dan Kebudayaan, 2023)
One third of Muslims in the European Union are in France. The development of Muslims in France is inseparable from Muslim immigrants from predominantly Muslim countries such as Tunisia, Morocco and Algeria. Islam is the second largest religion in France. So it can be one of the factors to win elections in France if candidates can win the hearts and votes of Muslims in France. This article will explain Emmanuel Macron's political strategy towards Muslims in France in the 2017 elections. The purpose of this research is to provide political views and effective political strategies to win the sympathy of Muslims in minority countries in Europe. The methodology used in writing this research is historical research methodology and in this research, researchers focus on library sources or library research, which is research that reveals facts through library data. The search results from various scientific studies reveal that in 2017 Emmanuel Macron won a landslide victory in the French elections defeating Le Pen with a presentation of 66.10 quoted from the Vie Punlique page published by the French Government's Department of Legal Information and Administration. and won the hearts of Muslim votes with a presentation of 92%. The strategy made by Emmanuel Macron was to make his image very good in front of French Muslims with his speeches during the election depicting that he was pro-Muslim and could provide a better life for French Muslims